2018
DOI: 10.1515/htmp-2016-0215
|View full text |Cite
|
Sign up to set email alerts
|

Research on Three-Roll Screw Rolling Process for Ti6Al4V Titanium Alloy Bar

Abstract: The effects of both the microstructure and the original grain size on three-roll screw rolling process of Ti6Al4V titanium alloy bar were studied in the present work. The microstructure of Ti6Al4V titanium bar had a great influence on the mechanical properties of the rolling bar. When the original size was large, the grains were apparently refined but the microstructure was uneven. But for semi-finished titanium bar composed of fine equiaxed grains, the grains after rolling were fine and uniform. During the ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 7 publications
(7 reference statements)
0
4
0
Order By: Relevance
“…The radial shear rolling (RSR) process is used for rolling round bars made of various metallic materials, including steel [ 17 , 18 ], titanium alloys [ 19 , 20 ], magnesium alloys [ 21 , 22 ], aluminum alloys [ 23 , 24 ] and zirconium alloys [ 25 ]. This process was developed at MISIS (National University of Science and Technology, Moscow, Russia) initially as a tube-forming process, and then adapted to produce round bars [ 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…The radial shear rolling (RSR) process is used for rolling round bars made of various metallic materials, including steel [ 17 , 18 ], titanium alloys [ 19 , 20 ], magnesium alloys [ 21 , 22 ], aluminum alloys [ 23 , 24 ] and zirconium alloys [ 25 ]. This process was developed at MISIS (National University of Science and Technology, Moscow, Russia) initially as a tube-forming process, and then adapted to produce round bars [ 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…The UTS reached 921 MPa, and TE was measured at 18.4%. X. Ding et al [ 19 ] controlled the original grain size through different heat treatment temperatures and then carried out a three-roll screw-rolling process and subsequent heat treatment on Ti-6Al-4V alloy bars. Finally, a material with significant differences in microstructure and mechanical properties was obtained, and the results showed that the bimodal microstructure with α grains accounting for about 40% had higher tensile strength when the area reduction rate was close.…”
Section: Introductionmentioning
confidence: 99%
“…These changes are due to the kinematic condition of the material helical flow [6]. The effects of the three-high RSR on the microstructure and properties formation were investigated for the following materials: titanium alloys [7][8][9][10], copper alloys [11], magnesium alloys [12][13][14][15], nickel alloys [16], zirconium alloys [17], and aluminum alloys [18,19]. The effect of the three-high RSR on the microstructure and properties formation was also studied when rolling steels of different chemical compositions and for different purposes [20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%